Peningkatan Hasil Belajar Pendidikan Pancasila Kelas IV Melalui Penerapan Model Talking Stick Berbantuan Media Question Box - Setiani, Faradilla; Rondli, Wawan Shokib; Ermawati, Diana (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The purpose of this research is to address the issue of low student performance in the Pancasila Education subject, as identified through observations and interviews at SD 1 Jepang. The Mid-Semester Assessment results showed that students did not meet the school's Learning Objective Completion Criteria of 75. This study aims to improve student learning outcomes in Pancasila Education by implementing the assisted talking stick model with the media question box.Method – The research method employed is Classroom Action Research, carried out in class IV at Elementary School 1 Jepang with 20 students over two cycles, each consisting of two meetings. Each cycle involves stages of planning, implementation, observation, and reflection. Data collection techniques include observation, interviews, tests, and documentation. The data is analyzed quantitatively based on test results and qualitatively through interviews and observations conducted in the pre-cycle.Findings – The results of this study demonstrate that the use of the Talking Stick model, supported by the Question Box media, can enhance student learning outcomes. This is evident from the success indicators, where student performance improved from 75% with